Policy Barriers to International Trade in Services : Evidence from a New Database - Borchert, Ingo; Gootiiz, Batshur; Mattoo, Aaditya (Oxford University Press on behalf of the World Bank, 2015)
Surprisingly little is known about policies that affect international trade in services. Previous analyses have focused on policy commitments made by countries in international agreements, but in many cases, these commitments do not reflect actual policy. This paper describes a new initiative to collect comparable information on trade policies for services from 103 countries across a range of service sectors and relevant modes of service delivery. The resulting database reveals interesting policy patterns. Although public monopolies are now rare and few services markets are completely closed, we observe numerous “second-generation” restrictions on entry, ownership, and operations. Even in instances in which there is little explicit discrimination against foreign providers, market access is often unpredictable because the allocation of new licenses remains opaque and highly discretionary in many countries. Across regions, some of the fastest-growing countries in Asia and the oil-rich Gulf states have restrictive policies in services, whereas some of the poorest countries are remarkably open. Across sectors, professional and transportation services are among the most protected industries in both industrial and developing countries, whereas retail, telecommunications, and even finance tend to be more open.